ANALISIS KEGAGALAN HANDOVER PADA SISTEM TELEKOMUNIKASI GSM DI PT. THREE (3) PONTIANAK - ., Zulpakar (Faculty of Engineering, Universitas Tanjungpura, 2016)
ABSTRACT- Handover is the switching frequency when the mobile station (MS) moves into regions or cells that have channels with different frequencies with previous cell so that the on going talks will not be interrupted. In the system handovers are not all of the handover process goes well, but of course many factors that can affect keberasilan handover is, in other words every handover failures are not only determined by Rx Level is not good, but on the quality of Rx Level very both can also be a failure of handover, because the quality is not very good RxQual. RxQual does very well also could affect the successful handover system. RxQual is not very good quality can be caused by azimutch, M-tilt and frequency interference at the BTS. Failure handover on site id 140 367 villages lime sector 2 to the site id 140 365 Bappeda sector 1 using TEMS version 11 were taken before and after optimization stages. The percentage HOSR obtained prior to optimization of 99.615% with enough categories, After optimization stages HORS percentage increased up to 100%. Failure handover on site towards the site Bapeda limestone villages because interference co-channal. Stages of optimization is to change the direction of azimutch, M-tilt and retune the frequency using the map info 11 version. Keywords: Handover, M-tilt. Rx Level, Rx Qual.